Masculinity, femininity and autistic traits - Chieng, Zhao Jing (2023)
Sex difference, i.e. biological sex has been studied quite extensively in Autism Spectrum Conditions (ASC). However, “gender” is multidimensional and not limited to the biological component of sex (Joel & McCarthy, 2016). Since gender tends to be viewed as non-binary more often by autistic than non-autistic people (Cooper et al., 2018), it is important to study other features of “gender” too. The current thesis focused on “gender role”, how much people align themselves with traditional masculinity and femininity traits. Categorized by stereotypes about gender, gender role is heavily influenced by the traditional social norms, which is in turn influenced by cultural values. This thesis aimed to discover the relationship between gender role and autistic traits, in addition to biological sex in neurotypical Malaysians.